2002
DOI: 10.1002/pd.257
|View full text |Cite
|
Sign up to set email alerts
|

The development of the fetal thymus: an in utero sonographic evaluation

Abstract: The present data offer the normal range of fetal thymus size from early stages of gestation that may allow intrauterine assessment of its development. It may be helpful in the prenatal diagnosis of thymic pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
116
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 11 publications
11
116
3
5
Order By: Relevance
“…The method proved successful in all cases but 1 regardless of fetal position. The positive linear correlation shown in this study is in close agreement with results published previously by us 3 and Paladini and Volpe. 18 As described in the latter study, 18 we also found that the combination of TUI and static VCI was preferable in terms of focus, calibration, and image detail, and this was applied to all volumes ( Figure 3, A and B).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The method proved successful in all cases but 1 regardless of fetal position. The positive linear correlation shown in this study is in close agreement with results published previously by us 3 and Paladini and Volpe. 18 As described in the latter study, 18 we also found that the combination of TUI and static VCI was preferable in terms of focus, calibration, and image detail, and this was applied to all volumes ( Figure 3, A and B).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, we found that in the sagittal plane, the vermis was very well delineated, and its longitudinal diameter could be measured. 3,17 This view may sometimes be difficult to obtain. Although in a vertex presentation, the vaginal approach can improve brain visualization, when the fetus lies in a breech presentation, it can require considerable time and expertise to obtain an adequate sagittal view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most prenatal sonographers will assess the TCD at axial sonography, coronal assessment has also been suggested 9 . Later, Zalel et al described sonographic measurements of the fetal vermis (width in the axial plane and height in the sagittal plane) 10 . Most recently Vinals et al have established biometry of the fetal cerebellar vermis, using volume contrast imaging in the coronal plane 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, normal biometric data were taken mainly from studies of PF biometry in ultrasonographic imaging. [8][9][10][11][12] However, MR imaging has advantages over sonography when assessing fetal PF, such as better accuracy when evaluating the vermis and better contrast resolution, which enable evaluation of the brain stem. 13,14 Therefore, during the past 2 decades, MR imaging has become an important tool to prenatally evaluate the morphology of the PF, and many studies have been published to supply valid MR imaging biometric data.…”
mentioning
confidence: 99%